Postpartum Uterine Prolapse in a Goat and its Successful Management - Singh, Bhoopendra; Singh, Kaushalendra Pratap; Kumar, Rajesh; Singh, Shubhendra Vikram; Husain, Safayat (Indian Journal of Veterinary Sciences and Biotechnology, 2020)
Postpartum uterine prolapse occurs in all animal species. It is most common in cows and ewe, less common in the  doe and rare in the mare. It is an eversion of the uterus, which  turns inside out as it passes through the vagina. Prolapse of  uterus generally occurs immediately after or a few hours of  parturition when the cervix is open, and the uterus lacks  tone (Hanie, 2006). The prolapse is visible as a large mass  protruding from the vulva, often hanging down below the  animal’s hock. The etiology of uterine prolapse is not yet  fully known. Hormonal imbalance, hypocalcemia, mineral  imbalances, injuries or stretching of birth passage, excessive  traction at assisted parturition, dystocia or forceful removal  of fetal membranes may contribute to the occurrence of  prolapse (Hanie, 2006; Jackson, 2004). Animals with uterine  prolapse should be treated promptly; otherwise, it may lead  to edema, ischemia, laceration, internal hemorrhage (Noakes  et al., 2001), prostration, and shock making prognosis poor to  hopeless. The success of treatment depends on the type of  case, the degree of damage, and contamination. The present  case highlights the successful management of postpartum  uterine prolapse in a goat.
Keywords: Clinical management; Goat; Postpartum; Uterine prolapse